2011
DOI: 10.1186/1471-230x-11-80
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol in therapeutic dosages and acute liver injury: causality assessment in a prospective case series

Abstract: BackgroundAcute liver injury (ALI) induced by paracetamol overdose is a well known cause of emergency hospital admission and death. However, there is debate regarding the risk of ALI after therapeutic dosages of the drug.The aim is to describe the characteristics of patients admitted to hospital with jaundice who had previous exposure to therapeutic doses of paracetamol. An assessment of the causality role of paracetamol was performed in each case.MethodsBased on the evaluation of prospectively gathered cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
0
42
0
1
Order By: Relevance
“…There may be several reasons for this: OTC paracetamol is usually not recorded in claims databases or in medical databases; and in field studies there may be under-ascertainment or dismissal of non-overdose paracetamol exposure. The hepatotoxicity of paracetamol has been generally thought to be confined to overdose [3, 28, 29], including staggered overdoses [30], although there have been studies showing an association of paracetamol at therapeutic doses and liver injury [3, 31, 32] in addition to case reports [33]. Others dispute this association [3436].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be several reasons for this: OTC paracetamol is usually not recorded in claims databases or in medical databases; and in field studies there may be under-ascertainment or dismissal of non-overdose paracetamol exposure. The hepatotoxicity of paracetamol has been generally thought to be confined to overdose [3, 28, 29], including staggered overdoses [30], although there have been studies showing an association of paracetamol at therapeutic doses and liver injury [3, 31, 32] in addition to case reports [33]. Others dispute this association [3436].…”
Section: Discussionmentioning
confidence: 99%
“…When this is compared with population exposure, in DDD or treatment-years, the event rates were 2- to 3-fold greater than with NSAIDs. This may be purely coincidental, and in most cases there may be another explanation [35], but non-overdose paracetamol might also play a direct or indirect causal role [31, 33], maybe through depletion of glutathione, reducing liver detoxification capabilities [37, 38]. Because paracetamol may be bought OTC in supermarkets and petrol stations (albeit in very small quantities), and this would not be captured in the UK, Ireland or The Netherlands, there could be concern about overestimation of the event rate for paracetamol.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute liver injury (ALI) was estimated from a retrospective study of cases that presented at 12 hospitals in Spain over a 6-year period 28. After establishing a likely causal link with paracetamol, the researchers estimated the incidence of ALI following use of paracetamol at therapeutic doses to be 10 per million paracetamol users per year (95% CI 4.3 to 19.4).…”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…Data on over 1000 patients including Malays, Chinese and Indians concluded that paracetamol-induced hepatotoxicity rates in a multiethnic Asian population was low at 7.3% and mortality and morbidity were non-existent despite high doses of paracetamol ingestion and delayed presentation [51].…”
Section: Hepatotoxicity In Asiansmentioning
confidence: 99%